Refugees as Innocent Bodies, Directors as Political Activists: Humanitarianism and Compassion in European Cinema - Ipek Celik-Rappas (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This article explores the ways in which refugees and humanitarianism appear in European film productions. It argues that European films often present images of innocent and victimized refugees in order to raise compassion of their liberal spectators. In the meanwhile their directors are praised for their humanitarian activism as they are considered to save refugees and their suffering from anonymity and placing their stories and humanity on the screen. Examining a number of European productions of the 2000s (Children of Men, Dheepan, In This World, Terraferma, and Welcome) this study suggests that politics of humanitarianism and of filmmaking on refugees share a similar problematic approach: in order to prove refugee eligibility for asylum and to raise compassion, they seek to establish the precarity and innocence of refugees, especially through showing their bodily pain.